Persistent Effects of Social Program Participation on the Third Generation - Gordon Dahl; Anne Gielen (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
Can participation in safety net programs have long-lasting negative effects across multiple generations? Prior work shows a 1993 Dutch disability insurance reform which tightened requirements and lowered benefits for participants resulted in better outcomes for their children. We study the third generation, finding that grandchildren of individuals whose DI eligibility and benefits were reduced are less likely to be born premature, have low birthweight, or experience complicated deliveries. They also have better health and schooling outcomes during early childhood. These early-life improvements are consequential, as they have been linked to better health, education, and labor market outcomes in adulthood.
Keywords: I38; H53; J62; 330; Multigenerational links; disability insurance; child health